FEATURES OF THE USE OF REPRODUCTIVE AND RESEARCH METHODS IN RUSSIAN LANGUAGE LESSONS. - Ismatullaev Abror Malikovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
the article reveals a number of methodological techniques that contribute to the activation of students in the Russian language class. The author gives a detailed analysis of the explanatory, heuristic, reproductive and research methods. The publication provides a thorough and detailed analysis of the advantages and disadvantages of the reproductive method.